PENERAPAN STRATEGI DIRECT READING THINKING ACTIVITY (DRTA) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN TEMA CITA CITAKU - Marlina, Anna; Pateda, Lamsike; Talango, Sitti Rahmawati (DIRASATUL IBTIDAIYAH, 2024)
AbstractThis research aims to improve the reading comprehension skills of fourth grade students through the application of the Direct Reading Thinking Activity (DRTA) strategy. Based on initial observations, the reading comprehension ability of class IV students is relatively low, seen from the low reading comprehension evaluation data, only 8 students reached the KKM out of 23 students. This type of research is Classroom Action Research (PTK). The subjects of this research were 23 class IV students. The Kemmis Mc Taggart model research design consists of 4 stages, namely: planning, implementation, observation and reflection. Data collection techniques use: tests, observation and documentation. The results of this research show that the Direct Reading Thinking Activity (DRTA) strategy can improve the reading comprehension skills of fourth grade students at SDN 19 Limboto. The average increase in the reading comprehension ability score in cycle I was 7.26, the initial condition was 57.52, increasing to 64.78, and the increase in cycle II was 20, the initial condition was 57.52, increasing to 84.78. The percentage of students who have achieved the KKM has increased from cycle I which was originally 60.86% to 86.95%.Keywords: Reading Comprehension, DRTA Strategy, Indonesian AbstrakPenelitian ini bertujuan untuk meningkatkan kemampuan membaca pemahaman siswa kelas IV melalui penerapan strategi Direct Reading Thinking Activity (DRTA). Berdasarkan observasi awal kemampuan membaca pemahaman pada siswa kelas IV tergolong rendah dilihat dari data hasil evaluasi membaca pemahaman yang rendah hanya 8 siswa yang mencapai KKM dari 23 siswa. Jenis Penelitian ini adalah Penelitian Tindakan Kelas (PTK). Subjek penelitian ini adalah siswa kelas IV yang berjumlah 23 siswa. Desain penelitian model Kemmis Mc Taggart yang terdiri dari 4 tahap yaitu: perencanaan, pelaksanaan, observasi serta refleksi. Teknik pengumpulan data menggunakan: tes, observasi dan dokumentasi. Hasil penelitian ini menunjukkan strategi Direct Reading Thinking Activity (DRTA) dapat meningkatkan kemampuan membaca pemahaman siswa kelas IV SDN 19 Limboto. Peningkatan rata-rata nilai kemampuan membaca pemahaman Pada siklus I sebesar 7,26 yang kondisi awal 57,52 meningkat menjadi 64,78 dan peningkatan pada siklus II sebesar 20 yang kondisi awa 57,52 meningkat menjadi 84,78. Presentase siswa telah mencapai KKM meningkat dari siklus I yang semula 60,86% meningkat menjadi 86,95%.Kata Kunci: Membaca Pemahaman, Strategi DRTA, Bahasa Indonesia